3D graphic organizers(Foldables) for vocabulary learning - Chafla Ruiz, Sandra Paulina (2022)
This research was carried out due to the importance of the acquisition of vocabulary to develop the skills and sub-skills in the process of learning the English language. It was applied to students in the third year of baccalaureate at Riobamba Educational Unit. At the beginning of the school year, it was observed that students had difficulty communicating, due to the poor vocabulary they knew. For this reason, this study is necessary, since the students need to transmit their thoughts and ideas effectively. Thus, this research aims to evaluate the effects of the didactic strategy 3D graphic organizers (foldables) when learning vocabulary. The methodology used was a mixed approach, descriptive, exploratory, and correlational methodology. In the state of the art, the most relevant concepts and the most important authors were considered. Additionally, to measure the effects of this implementation, a pre-test and a post-test were designed, as well as an observation card and a post-survey. In summary, the students mentioned that the use of the foldables was an innovative strategy in English language vocabulary learning. Five foldables were applied and proved to be effective in meeting the proposed objectives, the results of which were shown in the general graph, with a difference of approximately 23% more effective than the common techniques. The research concludes with a proposal for a didactic guide for teaching vocabulary through foldables.